Ulnar Nerve Granuloma Presenting as a Peripheral Nerve Sheath Tumor: A Case Report and Literature Review - Yue, John K.; Chen, Jia-Shu; Elguindy, Mahmoud M.; Tang, Vivian; Tripathy, Ryan; Bond, Allison R.; Aabedi, Alexander A.; Shah, Vinil N.; Perry, Arie; Bollen, Andrew W.; Lee, Dong Heun; Jacques, Line G. (Journal of Brachial Plexus and Peripheral Nerve Injury, 2025)
Peripheral nerve masses have a wide differential diagnosis; however, there is no established diagnostic framework for evaluating non-neoplastic etiologies, such as inflammatory or infectious lesions. Here, we present a rare case of an ulnar nerve granuloma that initially mimicked a peripheral nerve sheath tumor (PNST) on imaging and clinical presentation to elucidate the relevant medical history, imaging, and histology that aid in distinguishing inflammatory, infectious, and neoplastic peripheral nerve lesions. An 85-year-old man with melanoma and multiple prior right elbow surgeries presented with right-hand weakness and a rapidly enlarging gadolinium-enhancing ulnar nerve mass suggestive of a PNST that warranted surgical resection. Surgical histology showed a necrotizing granulomatous lesion that then became most concerning for a parasitic infection. However, broad serum and histologic testing by the Centers for Disease Control and Prevention were all ultimately negative. The final diagnosis was an inflammatory reaction to a retained foreign body from his prior elbow surgeries. In summary, surgery and comprehensive histologic workup are required for diagnosing granulomatous peripheral nerve lesions that mimic PNSTs on imaging and infection on histology.
Keywords: foreign body reaction; granuloma; infection; peripheral nerve sheath tumor; ulnar nerve